(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
This article contents analyses of some questions of lexicology. It was studied the function and character of loan-words and ways of their phonetically, morphologically and grammatically adaptation in German.